2017
DOI: 10.1103/physrevlett.119.036804
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Thermoelectric Current in Tubular Nanowires

Abstract: We calculate the charge current generated by a temperature bias between the two ends of a tubular nanowire. We show that in the presence of a transversal magnetic field the current can change sign, i.e., electrons can either flow from the hot to the cold reservoir, or in the opposite direction, when the temperature bias increases. This behavior occurs when the magnetic field is sufficiently strong, such that Landau and snaking states are created, and the energy dispersion is nonmonotonic with respect to the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 56 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…For topological insulator nanowires one can expect reversed, or anomalous, currents measured in tens of nanoamperes [ 11 ], well within experimental reach. Also, since the transport is over long systems, it is much simpler to maintain a large temperature difference of tens of kelvins, compared to the case of quantum dots.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For topological insulator nanowires one can expect reversed, or anomalous, currents measured in tens of nanoamperes [ 11 ], well within experimental reach. Also, since the transport is over long systems, it is much simpler to maintain a large temperature difference of tens of kelvins, compared to the case of quantum dots.…”
Section: Introductionmentioning
confidence: 89%
“…The charge current can of course be positive or negative depending on the charge of the carriers, i.e., whether they are electrons or holes. Recently, it was shown that in systems showing non-monotonic transmission properties the particle current can change sign as a function of the temperature difference [ 11 ]. Sign changes of the thermoelectric current are well-known in quantum dots [ 12 15 ] when the chemical potential crosses a resonant state.…”
Section: Introductionmentioning
confidence: 99%
“…The case with applied magnetic fields can be treated with an appropriate change of the momentum operator [206]. The eigenstates of Eq.…”
Section: Electron Transport In Nanowiresmentioning
confidence: 99%
“…The perturbative expansion of charge and heat current operators in Equations (13) and (40) allows for also expressing these quantities perturbatively in Λ, namely…”
Section: Mixed Noise and Heat Noisementioning
confidence: 99%
“…This observation is of particular importance in view of the progressive miniaturization of electronic devices, which makes the problem of heat transfer at the nanoscale extremely timely [24], as demonstrated by recent progress in the field of quantum thermodynamics [25]. In this framework, new intriguing challenges are posed by the need of properly transposing concepts such as energy harvesting [26][27][28][29][30][31][32][33], transport [34][35][36][37][38][39][40] and exchange [41][42][43] at the mesoscopic scale.…”
Section: Introductionmentioning
confidence: 99%